Optimization and modeling of bio-oil production from palm shell by pyrolysis using response surface methodology - Abnisa, F.; Daud, W.M.A.W.; Jaya Narayan, S. (2010)
Renewable energy is beneficial energy choice, more environmentally friendly, available in a wide variety of sources and capable regenerate within a short period of time. It is potential to replace fossil fuels as a dominant energy source. In this context, biomass appears as one important renewable source of energy. Biomass is the largest source in the world, available in several categories and easy to find in the surrounding environment. It is the only renewable energy source that can provide liquid fuels. In Malaysia, various types of biomass sources can be found easily, one of them is palm shell. Palm shell is one of the largest agriculture residues that can be categorized into the biomass. The objective of this work is to convert palm shell into bio-oil by using pyrolysis and to find the optimum condition to produce the highest yield of bio-oil. Several parameters which have effect to the process such as temperature, N2 flow rate, reaction time and particle size is will be investigated in this study. The response surface methodology (RSM) in conjunction with the central composite design (CCD) was used to determine the optimum value of the operating factors for maximum yield of bio-oil. In addition, the bio-oil obtained under the optimum condition was characterized by Fourier Transform infra-red (FT-IR) spectroscopy and gas chromatography/mass spectrometry (GCMS) techniques.